The Effectiveness of International Law in Limiting Humanitarian Disasters in the Palestine-Israel Conflict - Gunawan, Yordan; Pangestu, Rian Ade; Hardiyanti, Lista Arofa; Genovés , Manuel Beltrán (Lembaga Contrarius Indonesia, 2025)
The Israeli-Palestinian conflict involving several Arab and Western countries that has been going on for decades has caused a humanitarian disaster. The UN resolution to stop the conflict is also considered ineffective in resolving the conflict. Since the Hamas attack on October 7, 2023, against Israel, the conflict has reached its peak and caused a humanitarian disaster that certainly violates the 1947 Geneva Convention. Then, questions arose in the International Community about whether this conflict could be resolved. This research is a normative legal research with a Juridical Approach and a Case Approach. This research also uses a literature review that aims to critically examine the effectiveness of international law on the Israeli-Palestinian conflict so that the public can know the mechanisms that can be used to resolve the conflict. The results of the study show that this conflict can be resolved in several ways, such as by ratifying the 1947 Geneva Convention, then confirming the role of the UN, and also confirming the jurisdiction of the ICC in resolving this conflict.